Who’s Doing the Housework and Childcare in America Now? Differential Convergence in Twenty-First-Century Gender Gaps in Home Tasks - Melissa A. Milkie; Liana C. Sayer; Kei Nomaguchi; Hope Xu Yan (Socius)
Gender scholars have debated whether the recent movement toward a more equal division of domestic labor is stalling. Using a differential convergence perspective, the authors argue that examining which domestic tasks undergo gender convergence, whose changes narrow the gap, and why changes happen is critical for understanding gender inequalities in unpaid labor time. Using data from the 2003–2023 American Time Use Survey, the authors examine trends in total housework (including core and occasional housework), shopping, and childcare time. Results for married individuals indicate that the historically large gender gap in total housework time narrowed further this century, from a women-to-men ratio of 1.8:1 in 2003–2005 to 1.6:1 in 2022–2023. This shrinking of the gender gap was concentrated in traditionally feminine core housework (decreasing by 40 percent, from 4.2:1 to 2.5:1), particularly housecleaning and laundry. The gender difference in shopping time also narrowed, nearing parity. For childcare time, the gender gap shrunk from 2:1 to 1.8:1, though this change was not statistically significant. Decomposition analyses indicate that women’s reduced housework time was explained mainly by population compositional shifts, whereas men’s increased core housework time likely reflected behavioral or normative changes. With men taking on more female-typed domestic activities, the gendered norms associated with different forms of unpaid labor may be becoming redefined.